The advantage of fear stimuli in accessing visual awareness - Gomes, Nuno Miguel de Jesus (2016)
Snakes and spiders constitute evolutionary relevant stimuli for primates, having a privileged access to defense mechanisms (compared to innocuous stimuli). However, throughout evolution, these stimuli appear to have represented different threat levels. Snakes, as predicted by the Snake Detection Theory (Isbell, 2009), provoked a stronger evolutionary pressure than spiders, shaping the vision of primates towards their preferential processing, mainly in the most complex perceptual conditions. Several studies indicate that emotionally relevant and/or high arousal stimuli have faster access to visual awareness than stimuli without these features. Nevertheless, to the best of our knowledge, no studies have directly investigated the role of evolutionary pressure in this privileged access. Using continuous flash suppression (CFS), the present study assessed the role of evolutionary pressure in the access to visual awareness. For this purpose, we measured the time needed for three types of stimuli – snakes and spiders (matched with snakes for rated fear levels but for which an influenced on primate evolution is less well grounded), and birds (an innocuous animal stimulus) – to break the suppression caused by the CFS and access visual awareness in two different suppression intensity conditions. The results showed that in the less demanding suppression condition (i.e., stimuli presented to participants’ dominant eye) both evolutionarily relevant stimuli (snakes and spiders) had faster access to visual awareness than the bird stimulus, whereas in the most demanding suppression condition (i.e., stimuli presented to participants’ non-dominant eye) condition only snakes showed this privileged access. We propose that stimuli that suffered most evolutionary pressure show advantages in accessing to visual awareness. Our data suggests that the privileged processing of snakes in the most complex perceptual conditions extends to the access to visual awareness, corroborating the unquestionable value of snakes in the primates’ evolution.